State of Massachusetts-Bay. In the House of Representatives, March 17th, 1777 : Whereas it is indispensably necessary that the troops raised and raising ... for the Continental Army, should be as soon as possible furnished with good fire arms and accoutrements ... Resolved, that the selectmen of the several towns ... assist any soldier ... belonging to their respective towns ... in procuring the same . ([Printed by Benjamin Edes], 1777)
March 17, 1777 House resolutions which established the process for obtaining arms for the soldiers in the Continental Army.